Bioactivity of sol–gel-derived TiO2 coating on polyetheretherketone: In vitro and in vivo studies. (15th April 2016) - Shimizu, Takayoshi; Fujibayashi, Shunsuke; Yamaguchi, Seiji; Yamamoto, Koji; Otsuki, Bungo; Takemoto, Mitsuru; Tsukanaka, Masako; Kizuki, Takashi; Matsushita, Tomiharu; Kokubo, Tadashi; Matsuda, Shuichi
Graphical abstract: Abstract: A polyetheretherketone (PEEK) surface was modified using a sol–gel-derived TiO2 coating in order to confer bone-bonding ability. To enhance the bonding strength of the coating layer, pretreatment with either O2 plasma or sandblasting was performed prior to sol–gel coating. Additionally, post-treatment with acid was carried out to confer apatite (calcium phosphate)-forming ability to the surface. Biomechanical and histological analyses performed using an in vivo rabbit tibia model showed that PEEK surfaces modified with sol–gel-derived TiO2 and acid post-treatment had better bone-bonding properties than uncoated PEEK surfaces. These modified surfaces also performed well in terms of their in vitro cell responses due to their modified surface chemistries and topographies. Although O2 plasma or sandblasting treatment were, for the most part, equivocal in terms of performance, we conclude that sol–gel-derived TiO2 coating followed by acid post-treatment significantly improves the bone bonding ability of PEEK surfaces, thus rendering them optimal for their use in surgical implants. Statement of Significance: The role of polyetheretherketone (PEEK) as an alternative biomaterial to conventional metallic implant materials has become increasingly important. However, its low bone bonding ability is yet to be resolved. This in vivo and in vitro investigation on the functionalization of PEEK surfaces highlights the utility of this material in clinical interventions that require implants, and may extend range of applications of PEEK.